Solar redox cycling of ceria in a monolithic reactor for two-step H2O/CO2 splitting: Isothermal methane-induced reduction versus temperature-swing cycle - Anita Haeussler; Srirat Chuayboon; Stphane Abanades (My University, 2020)
Solar thermochemical cycles provide an efficient route to convert solar energy into valuable chemical energy carriers, such as solar fuels. The splitting of CO2 and H2O using metal oxide redox pairs permits to produce clean synthetic fuels. Furthermore, CO2 is upgraded into a valuable product (CO) that can be further converted to liquid hydrocarbon fuels when combined with H2. Among the possible candidate materials for two-step redox cycling, ceria appears promising given the high oxygen mobility and exchange property in the crystal lattice offering large amounts of oxygen vacancies (δ in CeO2-δ) while retaining fluorite structure, rapid and reversible transition between Ce4+ and Ce3+ oxidation states, and stable crystal structure during cycling. During a first step at high temperature, the metal oxide (CeO2) is reduced by releasing O2 thus creating oxygen vacancies in the ceria structure. In a second step at lower temperature, the non-stoichiometric oxide (CeO2-δ) is re-oxidized with CO2 or H2O, leading to the production of CO or H2 (solar fuels). This temperature-swing operating mode requires high temperatures during the reduction and a temperature gap between the two steps, which impacts the solar-to-fuel efficiency. The use of methane as reducing agent in the reduction step can be used to decrease the reduction temperature and allow isothermal operation. A comparison between the two operating modes, namely isothermal methane-induced reduction versus temperature-swing cycle, was performed in a monolithic solar reactor integrating ceria porous foams. The reduction of ceria using methane results in a higher reduction extent and fuel production with lower cycle temperatures (950-1050°C) at the expense of using a carbonaceous reducer. Thus, the temperature-swing operation appears as a more suitable long-term option for sustainable solar fuel production, but shows more stringent requirements on the reacting materials and solar reactor. The fuel production in the temperature-swing cycle was further increased by decreasing the pressure or increasing the reduction temperature, while the material performance stability was not altered after extended cycling.
Keywords: Thermochemical cycle; Isothermal process; Chemical-Looping Combustion; Solar fuel; Chemical Looping and Thermochemical Processes